Proses Rencana Manajemen Media Sosial dalam Publikasi Humas - Sofi Maulana; Choirus Sholihin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
In this journal, the researcher will explain how social media management is used as a public relations publication medium at the Assalafi Al Fithrah Islamic Boarding School in Surabaya, and will also explain what are the supporting and inhibiting factors in social media management as a public relations publication medium at the Assalafi Al Fithrah Islamic Boarding School in Surabaya. This study uses qualitative descriptive research. This type of qualitative research with a descriptive approach explains or describes what actually happened during the research. This study collected data using three methods, namely observation, interviews, and documentation. The results of this study found that 1) The media team of the Assalafi Al Fithrah Islamic Boarding School in Surabaya uses social media Instagram, Facebook, Twitter, and websites as public relations publication media. 2) Social media management as a public relations publication medium at the Assalafi Al Fithrah Islamic Boarding School in Surabaya is not running optimally, because the presentation of content is more focused on da'wah, while the publication of public relations activities and information is minimal. This is due to the lack of involvement of the Public Relations Acting Officer in social media management. 3) Supporting factors for social media management as a public relations publication medium are human resources who always improve their competence so they can always keep up with the times. Meanwhile, the inhibiting factors are human resources working independently, insufficient time for content creation, minimal institutional activity content, no role of public relations in content creation, no posting schedule, limited budget, and inadequate human resources so that the implementation is less than optimal.